Widespread underfilling of the potential ranges of North American trees. (11th November 2020) - Seliger, Benjamin J.; McGill, Brian J.; Svenning, Jens‐Christian; Gill, Jacquelyn L.
Abstract: Aim: Climatic equilibrium is a foundational principle in ecological theory and models used in conservation, but has been challenged by growing evidence of disequilibrium, particularly for long‐lived, sessile organisms like trees. Here, we calculated range filling for North American trees to detect the degree to which trees are filling their potential climatic niches, and to assess climatic and non‐climatic drivers of underfilling. Location: North America (22°N–72°N). Taxon: Trees and shrubs. Methods: We modelled the potential ranges of 447 North American tree and shrub species with species distribution models using bioclimatic variables, and calculated the occupied proportion of each potential range. Results were compared to a null model using simulated ranges generated by a spreading‐dye algorithm. We further used range shape ratios (latitude/longitude) to detect the drivers of disequilibrium. Results: The potential ranges of North American trees and shrubs are broadly underfilled (mean = 48%). Furthermore, range filling is positively correlated with geographic range size. Large‐ranged species have higher range filling than the null model, and shape ratios indicative of climatic restrictions. Small‐ranged species showed a stronger influence of dispersal limitation. Main conclusions: Climate explains only about half of tree species' ranges, and the signal of climatic equilibrium increases with range size. Small‐range species show high levels of climatic disequilibrium, which is likely be driven by combinations of dispersal lags, and undetected environmental factors or biotic interactions. These results highlight the importance of conserving small‐ranged species and the difficulty of forecasting how their distributions will shift in the coming centuries.